Adiponectin serum level is an independent and incremental predictor of all‐cause mortality after transcatheter aortic valve replacement. Issue 10 (6th August 2022) - Walpot, Jeroen; van Herck, Paul; Collas, Valerie; Bossaerts, Liene; Van de Heyning, Caroline M.; Vandendriessche, Tom; Heidbuchel, Hein; Rodrigus, Inez; De Block, Christophe; Small, Gary R.; Bosmans, Johan
Abstract: Background: Quantifiable biomarkers may be useful for a better risk and frailty assessment of patients referred for transcatheter aortic valve implantation (TAVI). Hypothesis: To determine if adiponectin serum concentration predicts all‐cause mortality in patients undergoing TAVI. Methods: 77 consecutive patients, undergoing TAVI, were analyzed. The CT axial slices at the level of the fourth lumbar vertebra were used to measure the psoas muscle area, and its low‐density muscle fraction (LDM (%)). To assess the operative risk, the STS (Society of Thoracic Surgeons Predicted Risk of Mortality) score, Log. Euroscore, and Euroscore II were determined. A clinical frailty assessment was performed. ELISA kits were used to measure adiponectin serum levels. We searched for a correlation between serum adiponectin concentration and all‐cause mortality after TAVI. Results: The mean age was 80.8 ± 7.4 years. All‐cause mortality occurred in 22 patients. The mean follow‐up was 1779 days (range: 1572–1825 days). Compared with patients with the lowest adiponectin level, patients in the third tertile had a hazards ratio of all‐cause mortality after TAVI of 4.155 (95% CI: 1.364–12.655) ( p  = .004). In the multivariable model, including STS score, vascular access of TAVI procedure, LDM (%), and adiponectin serum concentration, serum adiponectin level, and LDM(%) were independent predictors of all‐cause mortality after TAVI ( p  = .178, .303, .042, and .017, respectively). Adiponectin level was a predictor of all‐cause mortality in females and males ( p  = .012 and 0.024, respectively). Conclusion: Adiponectin serum level is an independent and incremental predictor of all‐cause mortality in patients undergoing TAVI.